Menjalin Silaturahmi Dengan Warga Serumpun Dalam Peningkatan Kualitas Hidup Dinegeri Seberang - Tangngisalu, Jannati; Alam, Syamsul; Daud, Dahniyar; Yusuf, Marwah; Razak, Nurlaely; Sufiati, Sufiati; Pongkapadang, Gunawan L.; Nuramal, Nuramal; Ilham, Muhammad (Journal Of Human And Education (JAHE), 2024)
Abstrak Suku Bugis adalah salah satu suku di Asia Tenggara yang termasuk ke dalam rumpun keluarga besar Austronesia dengan populasi lebih dari empat juta orang. Orang-orang bugis membangun koloni-koloni di Kalimantan bagian timur, bagian tenggara, Pontianak, Semenanjung Melayu. Kegiatan pengabdian ini bertujuan untuk menumbuhkan tali silaturahmi warga negara Indonesia khususnya suku bugis yang ada di Malaysia dalam meningkatkan kualitas hidup dirantau orang. Metode pelaksanaan program melalui shering session dengan warga diaspora yang ada di Malaysia. Hasil pelaksanaan kegiatan ini berupa Tindak lanjut kegiatan yang diharapkan lebih terjalinnya silaturahmi antar Warga Negara Indonesia yang ada di Malaysia khusus Suku Bugis dimana naungan Perhimpunan Bugis Johor Kata Kunci: Suku Bugis, Indonesia, Malaysia, Perhimpunan Bugis Johor. Abstract The Bugis tribe is one of the tribes in Southeast Asia that belongs to the large Austronesian family with a population of more than four million people. Bugis people built colonies in eastern Kalimantan, southeast, Pontianak, Malay Peninsula. This service activity aims to foster the relationship between Indonesian citizens, especially the Bugis tribe in Malaysia, in improving the quality of life overseas. The method of implementing the program is through a sharing session with diaspora residents in Malaysia. The results of the implementation of this activity are in the form of follow-up activities which are expected to further establish the relationship between Indonesian citizens in Malaysia, especially the Bugis tribe under the auspices of the Johor Bugis Association. Keywords: Bugis Tribe, Indonesia, Malaysia, Bugis Johor Association.